The role of geography's concepts and powerful knowledge in a future 3 curriculum - Maude, Alaric (International research in geographical and environmental education, 2020)
This article examines whether geography can provide the powerful knowledge that is a key element of a Future 3 curriculum, and an important component of the GeoCapabilities Project's proposals for the teaching of geography. Powerful knowledge is knowledge that gives students the intellectual ability to analyse, explain, predict, evaluate and think about the world in ways that are beyond their personal experience. The article focuses on two aspects of this knowledge. The first is the use of concepts to think in new ways, and the second is the ability to make generalisations and apply them to new contexts. The article also reviews and responds to arguments that geography's concepts cannot produce powerful knowledge. It concludes that geography in a Future 3 curriculum would emphasise building student understanding of geographical ways of thinking, based on its major concepts and their application. This understanding can be developed through a wide range of content, varying from place to place in an appropriately geographical way.